Analysis Of Early Marriage In Adolescents In Terms Of Ed-Ucation And Level Of Knowledge About Free Sex in Baho-Mante Village - Putri Eka Sejati; Fitriah (Master of Public Health Program Universitas STRADA Indonesia, 2023)
Marriage at an early age is still common in developing countries, one of which is Indonesia. Most people are not aware of the dangers of pregnancy or giving birth to mothers who are less than 20 years old. In Morowali district, the National Population and Family Planning Agency (BKKBN) of Central Sulawesi Province stated that the number of early child marriages in the region is still very high. From the overall data, there is 58% dominance of early marriage, in fact, this number in the last two years has moved up rapidly. The purpose of this study was to analyze the relationship between early marriage in adolescents in terms of education and level of knowledge about free sex in Bahomante Village, Bungku Tengah District, Morowali Regency.The research design used in this study is correlational analytic with a cross-sectional time approach. The population in this study were all young men and women aged 11-19 years in Bahomante Village, Bungku Tengah District, Morowali Regency in 2022. The sampling method in this study used a simple random sampling technique. Collecting data using a questionnaire. It is known that from 36 (100%) respondents the level of adolescent education is mostly high school and PT 28 (77.8%), most have good knowledge 28 (77.8%) and most are not married at an early age 28 (77, 8%). The analysis test using Chi Square shows that the significance level is 0.000 < = 0.05 so that H0 is rejected and H1 is accepted. Thus, there is a relationship between education and level of knowledge about free sex with early marriage in Bahomante Village, Bungku Tengah District, Morowali Regency. It is concluded that lack of education and knowledge is a factor in the occurrence of marriage at an early age. Most of the teenagers in Bahomante Village, Bungku Tengah District, Morowali Regency did not get married at an early age.